2012
DOI: 10.1029/2012gl052204
|View full text |Cite
|
Sign up to set email alerts
|

Constraining cloud lifetime effects of aerosols using A‐Train satellite observations

Abstract: [1] Aerosol indirect effects have remained the largest uncertainty in estimates of the radiative forcing of past and future climate change. Observational constraints on cloud lifetime effects are particularly challenging since it is difficult to separate aerosol effects from meteorological influences. Here we use three global climate models, including a multiscale aerosol-climate model PNNL-MMF, to show that the dependence of the probability of precipitation on aerosol loading, termed the precipitation frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
243
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 145 publications
(268 citation statements)
references
References 50 publications
23
243
2
Order By: Relevance
“…Until climate models are able to resolve clouds and convection, this approach may be worth pursuing. Alternatively, the multimodel framework [e.g., Wang et al, 2012] or new probability distribution function approaches to representing subgrid turbulence [Larson and Golaz, 2005] may prove useful.…”
Section: Discussionmentioning
confidence: 99%
“…Until climate models are able to resolve clouds and convection, this approach may be worth pursuing. Alternatively, the multimodel framework [e.g., Wang et al, 2012] or new probability distribution function approaches to representing subgrid turbulence [Larson and Golaz, 2005] may prove useful.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 1, Wang et al [2011a] replaced the very simple representation of cloud droplets and ice crystals of the original SP-CAM with a more general treatment that allows the number of droplets and crystals in clouds to respond more realistically to changes in aerosol particles produced by human activities, and the aerosol particles are now allowed to respond to cloud updrafts, chemical processing in droplets, and removal from the atmosphere by precipitation explicitly simulated by CRM (through a subsidiary model called Explicit Clouds and Parameterized Pollutants (ECPP)). These changes permit estimates of the impact of cloud-aerosol-precipitation interactions on the global energy balance [Wang et al, 2011b] that have been shown to be significantly more realistic than previous estimates [Wang et al, 2012].…”
Section: Recent Sp-cam Developmentsmentioning
confidence: 96%
“…Precipitation susceptibility has been proposed to evaluate aerosol-cloud-precipitation interactions and to further constrain the cloud water response to aerosol perturbations in cli-mate models (Feingold and Siebert, 2009;Terai et al, 2012;Wang et al, 2012). It was first proposed by Feingold and Siebert (2009) and was defined as…”
Section: Introductionmentioning
confidence: 99%
“…Sorooshian et al (2009) further estimated S 0 by replacing CDNC with aerosol index (AI). Wang et al (2012) proposed an alternative metric, the precipitation frequency susceptibility, defined as…”
Section: Introductionmentioning
confidence: 99%